Keeping up with the times: revising the dermatology residency curriculum in the era of molecular diagnostics and personalized medicine. (10th September 2014) - LaChance, Avery; Murphy, Michael J.
Abstract Background The clinical use of molecular diagnostics, genomics, and personalized medicine is increasing and improving rapidly over time. However, medical education incorporating the practical application of these techniques is lagging behind. Although instruction in these areas should be expanded upon and improved at all levels of training, residency provides a concentrated period of time in which to hone in on skills that are practically applicable to a trainee's specialty of choice. Although residencies in some fields, such as pathology, have begun to incorporate practical molecular diagnostics training, this area remains a relative gap in dermatology residency programs. Methods Herein, we advocate for the incorporation of training in molecular diagnostics and personalized medicine into dermatology residency programs and propose a basic curriculum template for how to begin approaching these topics. Results/Conclusions By incorporating molecular diagnostics into dermatology residency training, dermatologists have the opportunity to lead the way and actively shape the specialty's transition into the era of personalized medicine.